2020
DOI: 10.1177/0954406220939609
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and evaluation of dry and minimum quantity lubricating methods on machinability of AISI 4140 using Taguchi design and ANOVA

Abstract: In this work, it is aimed to study the effects of dry machining and minimum quantity lubrication application on machinability in turning AISI 4140 steel by utilizing different cutting parameters. Also, this study contains effects and optimization of cutting conditions (dry and minimum quantity lubricating), feed rate, and cutting speed on surface roughness (Ra) and main cutting forces (Fc) determined by employing the Taguchi method. At the end of experiments, it was established that compared to dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…In this paper, variance analysis, according to more commonly known name ANOVA, was used to evaluate the statistical importance and contribution rate on the output parameters. 82 The analysis was performed using Minitab software. A detailed explanation about the procedure of the practice of this method was given in the previous works of the author.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, variance analysis, according to more commonly known name ANOVA, was used to evaluate the statistical importance and contribution rate on the output parameters. 82 The analysis was performed using Minitab software. A detailed explanation about the procedure of the practice of this method was given in the previous works of the author.…”
Section: Discussionmentioning
confidence: 99%
“…The Taguchi method is an optimization method and experimental design based on factor design, tolerance design and system design. In addition, it is used to determine the optimal parameters from different levels [4,9,[28][29][30][31][32]. In the manufacturing industry, the time required for the product can be reduced by using the Taguchi method, thus reducing the costs and in-creasing the profit rate of the business.…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Regression analyses are carried out to analyse and model different variables that have a relationship between the dependent variable and the independent variables (one or more) [26,27,[35][36][37][38][39][40][41][42]. In this study, equations were found by regression analysis for the estimation of axial shortening and tensile strength.…”
Section: E Analysis Of Regressionmentioning
confidence: 99%